Building Religious Moderation Amid the Buzzer Raid - Ummy Chairiyah; Fikry Zahria Emeraldien (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In this digital era, cases of SARA (ethnic, race, and religions) are increasing, this is one of the negative impacts of digital disruption. Specifically, the presence of the internet caused SARA become easier to find, social media platforms and online news portals have become tools for the spread of hoax and hate speech, behind it all there are people who are referred as buzzers. This study aims to show how the role of the buzzer in disseminating information and inhibiting the spread of religious moderation among the Islamic community. This study uses a descriptive qualitative approach. The research data was collected purposively and preferably sourced from literature studies and documents that examine the buzzer phenomenon in Indonesia. The results of the research show that in this digital era, buzzers are troubling and threatening the nation. Buzzers have a strong position because of the influence and large following they have. Public awareness is important because from there we can unite to fight buzzer attacks. But the buzzer is not completely negative, the buzzer can also be used to spread positive da'wah messages.